Childhood Neurotic Traits - Shakya, Dhana Ratna (Journal of Nepal Paediatric Society, 2008)
‘Child is the father of a man.’ As Wordsworth has rightly said, the behavior and nature of a man is largely the continuation of them over the life span though there is some variation in the degree. So, the psychiatric assessment of a person is never complete without assessment of childhood neurotic traits. Even though there is tendency to omit the personal history (including childhood neurotic traits) in busy settings like the OPD, the presenting problem at times may be related to childhood neurotic traits in one or other way. Here, an attempt will be made to review the literature regarding ‘childhood neurotic traits’. J. Nepal Paediatr. Soc. Vol.28(1) p.27-29